Opal phytolith and isotopic studies of "Restinga" communities of Maricá, Brazil, as a modern reference for paleobiogeoclimatic reconstruction - Dos Santos, Catia Pereira (2015)
The Maricá restinga, located in the eastern part of the Rio de Janeiro State (Brazil), corresponds to one of the few remaining preserved areas of the state´s coastal plain. This paper reports on a study of the Maricá restinga plant communities and also presents an identification of the main plant species present in each community, with the objective of establishing reference collections, by the methods of the proxies opal phytoliths and stable carbon isotopes, for paleoenvironmental reconstructions of this coastal area during the Quaternary. Six plant communities, distributed perpendicularly to the coast line over sandy barriers, lagoonal plain, lagoon margin and weathered basement were identified: halophile-psamophile, scrub, herbaceous swamp, slack, shrubby vegetation and dry forest. In general, the plant species analyzed in each community presented low productivity of opal phytoliths, as only thePoaceae, Cyperaceae and Arecaceae families produce a great amount and diversity of morphotypes of opal phytoliths. The results of the analysis of stable carbon isotopes in sediments indicated a predominance of C3 or a mixture of C3 and C4 plants, presenting a close correlation with the results found in plants collected in each community. In conclusion, it was verified that the carbon isotope analysis associated with that of the opal phytoliths are good proxies for the reconstruction of vegetation in the study area.